STRATEGI PEMBELAJARAN BAHASA ARAB YANG EFEKTIF DI ERA DIGITAL - Zikrullah, Nuzuli; Afrah, Nurdina (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The development of digital technology has affected various aspects of life, including education. Arabic language learning as one of the important languages in the context of religion and science has also undergone a transformation. This research aims to explore effective Arabic learning strategies in the digital era. Using literature study and limited field observation, it is found that the integration of technology in the teaching and learning process such as the use of apps, social media, and multimedia-based learning can significantly increase students' interest and understanding. Interactive, flexible, and adaptive learning is the key to facing the challenges of learning Arabic in the digital era